1982
DOI: 10.1111/j.1469-8137.1982.tb03389.x
|View full text |Cite
|
Sign up to set email alerts
|

A MORPHOLOGICAL STUDY OF BUD INITIATION IN THE BROWN ALGA SPHACELARIA FURCIGERA*

Abstract: SUMMARYBud initiation and development in Sphacelaria furcigera involves the de-differentiation of a quiescent axial cell. This entails loss of cytoplasmic vacuoles and an increase in cytoplasmic mass and density. Cytoplasmic pressure in conjunction with a loosening ofthe outer longitudinal cell wall contributes to the formation of a bud protrusion. Incorporation of new cell wall material into the outer longitudinal cell wall allows the continued expansion of the bud protrusion. Pre-mitotic migration of the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
5
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
(36 reference statements)
5
5
0
Order By: Relevance
“…The results of the histochemical tests seem then to correlate well with our previous electron microscopic observations (Burns et al, 1981) in which cell wall layers CWl, CW3 and CWO were found to be primarily composed of amorphous material (fucans) and cell wall layers CW2, CW4, and CWI to be primarily composed of oriented microfibrils (alginates). Bud initiation appears to be characterized by a weakening/loosening ofthe cell wall in the vicinity of the bud protrusion and by a reduction in the number of cell wall layers from four to two during subsequent expansion (Burns et al, 1981). The reduction to two cell wall layers during bud expansion is probably related to an increase in cell wall pliability, a condition that is far more suitable for cellular growth and morphogenesis.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The results of the histochemical tests seem then to correlate well with our previous electron microscopic observations (Burns et al, 1981) in which cell wall layers CWl, CW3 and CWO were found to be primarily composed of amorphous material (fucans) and cell wall layers CW2, CW4, and CWI to be primarily composed of oriented microfibrils (alginates). Bud initiation appears to be characterized by a weakening/loosening ofthe cell wall in the vicinity of the bud protrusion and by a reduction in the number of cell wall layers from four to two during subsequent expansion (Burns et al, 1981). The reduction to two cell wall layers during bud expansion is probably related to an increase in cell wall pliability, a condition that is far more suitable for cellular growth and morphogenesis.…”
Section: Discussionsupporting
confidence: 87%
“…1) identical to that observed with the transmission electron microscope (Burns et al, 1981). At the onset of bud initiation, four distinct layers are recognized.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations